Research Interest in Pediatric Emergency Medicine Fellows. Issue 2 (February 2020) - Michelson, Kenneth A.; Nigrovic, Lise E.; Nagler, Joshua; McAneney, Constance M.; Mistry, Rakesh D.
Abstract : Objective: Factors predictive of research career interest among pediatric emergency medicine (PEM) fellows are not known. We sought to determine the prevalence and determinants of interest in research careers among PEM fellows. Methods: We performed an electronically distributed national survey of current PEM fellows. We assessed demographics, barriers to successful research, and beliefs about research using 4-point ordinal scales. The primary outcome was the fellow-reported predicted percentage of time devoted to clinical research 5 years after graduation. We measured the association between barriers and beliefs and the predicted future clinical research time using the Spearman correlation coefficient. Results: Of 458 current fellows, 231 (50.4%) submitted complete responses to the survey. The median predicted future clinical research time was 10% (interquartile range, 5%–20%). We identified no association between sex, residency type, and previous research exposure and predicted future research time. The barrier that most correlated with decreased predicted clinical research time was difficulty designing a feasible fellowship research project (Spearman coefficient [ρ], 0.20; P = 0.002). The belief that most correlated with increased predicted clinical research time was excitement about research (ρ = 0.69, P < 0.001). Conclusions: Most fellows expect to devote a minority of their career to clinical research. Excitement about research was strongly correlated with career research interest. Abstract : Supplemental digital content is available in the text.